Military Tribunate in the Careers of Roman Senators of the Severan Period. Part 4: Governorships of Praetorian and Consular Provinces - Okoń, Danuta (Polskie Towarzystwo Filologiczne, 2023)
Under the Principate, senatorial governorships of provinces were either of the praetorian or the consular rank. A military tribunate in the cursus honorum facilitated the award of the governorship of a province with legions, and subsequently a consulship and a proconsulship of either Asia or Africa. Although the military tribunate was not a compulsory office, its impact was evident at all stages of a senatorial career.